Thermal Elastohydrodynamic Lubrication Analysis of Bevel Gear based on a Finite Line Contact Model - Cong Wei; Youqiang Wang; Yabo Zhou; Shenwen Long (Jixie chuandong)
In order to study the thermal elastohydrodynamic lubrication mechanism of bevel gears， based on the theory of elastohydrodynamic lubrication， a finite line contact model is established and the thermal elastohydrodynamic characteristics of straight bevel gears are studied. Firstly， the problem of the thermal elastohydrodynamic lubrication of the straight bevel gear is approximately equivalent to the pseudo-steady state thermal elastohydrodynamic lubrication problem of the two-way tapered roller. The multi-grid method and the sequential sweeping method are used to solve the oil film pressure， the oil film thickness and the temperature of the solid and oil film middle layers on the entire contact line of the bevel gear. The results show that the pressure， film thickness and temperature of the straight-toothed bevel gears are not the same at all points along the direction of tooth width. Among them， the oil film pressure of the small end is slightly larger than the oil film pressure of the big end， the oil film thickness of the small end is smaller than the oil film thickness of the big end， the temperature distribution difference along the tooth width direction is more obvious， and the temperature of the middle layer of the oil film is greater than the temperature of the two solid surfaces. A theoretical basis for the lubrication design of straight bevel gear is provided by this study.